Copper catalyzed asymmetric synthesis of chiral allylic esters. - Geurts, K; Fletcher, S; Feringa, B (2006)
The complex derived from Taniaphos ligand 4 and CuBr*Me2S catalyzes the asymmetric addition of Grignard reagents to 3-bromopropenyl esters 1 to provide allylic esters 2 in high yields and high chemio-, regio-, and enantioselectivities. The work demonstrates that allylic asymmetric alkylation (AAA) can be done on substrates bearing a heteroatom at the gamma-position. The method is a practical route to chiral, nonracemic allylic alcohols. The use of functionalized substrates 1 or Grignard reagents leads to more complex products 2, which can be further manipulated as demonstrated in conversion to (S)-5-ethyl-2(5H)-furanone 6 and (S)-benzoic acid-cyclopent-2-enyl ester 7.